Microtubule configurations during fertilization, mitosis, and early development in the mouse and the requirement for egg microtubule-mediated motility during mammalian fertilization. - Schatten, G (1985)
Microtubules forming within the mouse egg during fertilization are required for the movements leading to the union of the sperm and egg nuclei (male and female pronuclei, respectively). In the unfertilized oocyte, microtubules are predominantly found in the arrested meiotic spindle. At the time for sperm incorporation, a dozen cytoplasmic asters assemble, often associated with the pronuclei. As the pronuclei move to the egg center, these asters enlarge into a dense array. At the end of first interphase, the dense array disassembles and is replaced by sheaths of microtubules surrounding the adjacent pronuclei. Syngamy (pronuclear fusion) is not observed; rather the adjacent paternal and maternal chromosome sets first meet at metaphase. The mitotic apparatus emerges from these perinuclear microtubules and is barrel-shaped and anastral, reminiscent of plant cell spindles; the sperm centriole does not nucleate mitotic microtubules. After cleavage, monasters extend from each blastomere nucleus. The second division mitotic spindles also have broad poles, though by third and later divisions the spindles are typical for higher animals, with narrow mitotic poles and fusiform shapes. Colcemid, griseofulvin, and nocodazole inhibit the microtubule formation and prevent the movements leading to pronuclear union; the meiotic spindle is disassembled, and the maternal chromosomes are scattered throughout the oocyte cortex. These results indicate that microtubules forming within fertilized mouse oocytes are required for the union of the sperm and egg nuclei and raise questions about the paternal inheritance of centrioles in mammals.